EFFECT OF NITROGEN, BIO-FERTILIZER AND F TILIZER AND FARM YARD MANURE ON YIELD AND NUTRIENT UPTAKE IN OAT (AVENA SATIVA L.) - VERMA, CHANCHAL; THANKI, J. D.; SINGH, DESHRAJ (The Bioscan, 2016)
An experiment with Four levels of nitrogen (0, 60, 120 and 180 kg/ha), two levels of bio-fertilizer (No biofertilizer (B0) and bio-fertilizer inoculation (B1 )) and two levels FYM (0 and 10 tonnes/ha) was conducted to study the effect of nitrogen, bio-fertilizer and FYM on yield and nutrient uptake of oat (Avena sativa L.). Significantly highest seed (54.02 and 51.90 q/ha) and straw (111.17 and 108.82 q/ha) yields, N (85.42 kg/ha), P (24.58 kg/ha) and K (44.61 kg/ha) uptake by seed, N (132.94 kg/ha), P (27.07 kg/ha)and K (105.25 kg/ha) uptake by straw were recorded with application 180 (N3 ) and 120 N/ha (N2 ) over control (N0 ) being remained at par with each other. Azotobacter inoculation (B1) recorded significantly highest seed (48.05q/ha) and straw (105.24 q/ha) yields, highest N (78.69 kg/ha), P (22.66 kg/ha) and K (41.07 kg/ha) uptake by seed, N (127.35 kg/ha) uptake by straw were observed with Azotobacter inoculation (B1) over no inoculation (B0). FYM application at 10 tonnes/ha (F1) significantly increased seed (49.97 q/ha) and straw (106.60 q/ha) yields, N (81.63 kg/ha), P (23.65 kg/ha) and K (42.91 kg/ha) uptake by seed and N (129.35 kg/ha), P (26.40 kg/ha)and K (102.98 kg/ha) uptake by straw over control (F0).